Benchmarking & penetration testing of Windows XP, Windows 7, Windows 8 - Tahir, Farhaj (2013)
The purpose of this study is to propose a unified approach for Operating System (OS) Comparisons with the help of a Windows OS case study. As based on current industry practice where most of the researchers; when comparing OS, either choose benchmarking to benchmark the hardware level performance or do penetration testing for checking security features of the OS. It is not known whether the latest OS is in fact faster and secure than its predecessors. A fair comparison of OS should include hardware level, operational level performance and security tests altogether. Thus, this research is aiming to integrate different aspects of the operating systems into comparison process which were neglected before to achieve a complete comparison result. Hardware level, operational level and security related tests were performed on Windows XP, Windows 7 and Windows 8 and the results indicate that there are instances where Windows XP excels over its counterparts. In overall Windows 8 is a superior OS to its predecessors which performs better and provide more security on the same hardware. Furthermore, from this research we can conclude that the automated benchmarking tools are proving to be less efficient to benchmark systems which are running on Windows XP and older OS as they do not support DirectX 11 and other advanced features which the hardware could support. Therefore, there lies the need of the unified approach to compare other aspects of OS such as user oriented tasks and security parameters to provide complete comparison data. As a future work, the method can be used as a guideline to propose a new benchmarking and penetration testing software.